2017
DOI: 10.1038/s41598-017-01635-1
|View full text |Cite
|
Sign up to set email alerts
|

Engineered HSV vector achieves safe long-term transgene expression in the central nervous system

Abstract: Previously we reported a new series of highly defective herpes simplex virus type 1 (HSV-1) vectors that were functionally devoid of all viral immediately early (IE) genes, resulting in virtual absence of viral gene expression. Nevertheless, a reporter gene cassette inserted into the vector flanked by boundary elements from the viral latency locus showed high, persistent reporter gene activity in nonneuronal cells while an independent expression cassette inserted into a deleted ICP4 locus remained almost silen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 22 publications
(35 reference statements)
2
30
0
Order By: Relevance
“…The suggestion that rDRGs in culture are relatively supportive of gene expression from highly defective HSV backbones agrees with our previous observation that an IE gene-inactive vector containing CAG-EGFP in the UL3-UL4 intergenic region produced substantially more EGFP-positive cells per input gc in rDRGs at 3 dpi than in nonneuronal cells (7). In contrast, we did not detect EGFP expression in rat hippocampus from the UL3-UL4 locus in previous work (31). Likewise, while CAG-EGFP in the LAT locus was active in cultured DRG neurons (reference 7 and this study), hippocampal expression was not observed (but see below).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The suggestion that rDRGs in culture are relatively supportive of gene expression from highly defective HSV backbones agrees with our previous observation that an IE gene-inactive vector containing CAG-EGFP in the UL3-UL4 intergenic region produced substantially more EGFP-positive cells per input gc in rDRGs at 3 dpi than in nonneuronal cells (7). In contrast, we did not detect EGFP expression in rat hippocampus from the UL3-UL4 locus in previous work (31). Likewise, while CAG-EGFP in the LAT locus was active in cultured DRG neurons (reference 7 and this study), hippocampal expression was not observed (but see below).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, very little, if any, EGFP signal was detected at any time point. These results indicated that A2UCOE can enhance transient, independent expression of a second transgene in the central nervous system to complement the previously described durable expression of a first transgene positioned in the deleted ICP4 locus (31,32). It remains to be determined what mechanisms can account for the rapid or immediate silencing of the LAT-based EGFP cassette of these vectors in mouse hippocampus.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…In addition, at variance with the previous results mentioned above, the deletion of ICP0 does not prevent transgene expression from a specific locus, ICP4. When the expression cassette was inserted in ICP4, a robust, sustained and neuron-specific transgene expression was observed in several rat brain regions, and this was clearly detectable for at least 6 months after vector injection with no detectable sign of neuronal toxicity or immune response (Verlengia et al, 2017 ). A further refinement of this vector was obtained through the additional removal of the virion host shutoff (vhs) gene (Figure 2A ), a strategy that further increased both the levels of transgene expression in neurons and the safety profile of the vector (Miyagawa et al, 2017 ).…”
Section: New Gene Therapy Vectorsmentioning
confidence: 99%
“…Our studies demonstrated prolonged, non-toxic transgene expression from a foreign promoter inserted directly downstream from the LAT promoter/enhancer region in non-neuronal cells. Interestingly, although expression from the LAT region was transient in rDRG cultures and largely undetectable in mouse hippocampus [ 104 , 105 ], reporter expression from the deleted ICP4 locus without adjacent LAT regulatory elements persisted for months in mouse hippocampus [ 106 ]. Furthermore, we observed that this expression could be further enhanced by deletion of the virion host shutoff gene (vhs or UL41) [ 104 ].…”
Section: Replication-defective Hsv Vectorsmentioning
confidence: 99%